Estudo do potencial antiinflamatório da clorexidina na gengivite associada ao aumento gengival humana, mediante avaliações clínicas, histológicas e imunohistoquímicas - Feitosa, Maria Gisélia Pinheiro (2006)
Gingival hyperplasia is an oral condition whose origin is attributed to the interaction of multiple factors: among them, genetic susceptibility; hormonal influences during puberty and pregnancy; therapy with drugs as varied as phenontoin, cyclosporine, diltiazen and anphetamines; action of proinflammatory cytokines, as TNF-α; and even neoplastic causes. Although excessive accumulation of dental plaque and chronic gingivitis have been included among predisposing factors for gingival hyperplasia, it is not yet known if preexisting gingivitis stimulates the gingival growth, or the hypertrophy promotes, due to the difficulties in dental hygiene, the accumulation of bacterial plaque and the consequent gingivitis, predisposing the individual to destructive periodontal disease. This study had the objective of evaluating if gingivitis is present in all gingival hyperplasia patients, and if the inflammation process responds satisfactorily to chlorhexidine treatment. Fourteen patients who were to undergo voluntary surgical treatment for gingival hyperplasia consented to participate in the study. The initial gingival biopsies were obtained from the patients before they underwent gingivectomy, to evaluate the inflammatory process by histology (H&E), and immunohistochemistry by Peroxidase-Anti-Peroxidase (PAP) method, utilizing monoclonal antibodies to cell markers CD43 (T cells), CD20 (B cells) and CD68 (macrophages). The patients were subsequently induced to perform mouthrinses 30 minutes after dental higiene, with 0.12% chlorhexidine for 30s during 10 days. Biopsies were then obtained from the gingival tissue removed by gingivectomy, for fresh histology and PAP evaluations. The results were as follows: i) all the patients with hyperplasia had ginigival inflammation in evolution, of histological grades 1 to 3; ii) the inflammatory process revealed presence of T cells (5.7 ± 2.07 per 6 microscopic fields), B cells (9.0±4.64), and macrophages (62.6± 16.44); iii) chlorhexidine treatment resulted histological reduction of inflammation, with a 40% decrease in macrophages (40.5 ± 9.15; p=0.05), and a moderate rise in T (8.25± 1.71) and B (12.75 ± 6.99) cells in the gingival tissue, revealing a decreased participation of macrophages, and possibly an increased engagement of lymphocytes in defenses. These observations suggest that there is a definite association between gingival hyperplasia and gingivitis, and that mouthrinses of chlorhexidine can be effective in diminishing the severity of gingival inflammation, in a majority (59%) of individuals.